2012
DOI: 10.4236/fns.2012.34067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partially De-Oiled Peanut Meal Flour (DPMF) on the Nutritional, Textural, Organoleptic and Physico Chemical Properties of Biscuits

Abstract: Partially de-oiled peanut meal flour (DPMF) was blended with wheat flour for making biscuits. DPMF at 5, 10, 15 and 20% was used to partially replace wheat flour in biscuits formulation and biscuits thus made were evaluated for nutritional composition, physical characteristics and sensory quality. Chemical analysis of DPMF showed 30.26% crude protein, 10.1% crude fat and 43.65% carbohydrates. The protein content increased nearly 1.5 times in biscuits as a result of incorporated DPMF, coupled with increase in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 18 publications
7
21
0
Order By: Relevance
“…This result was in accordance with the results of Nassar et al (2008) and Omoba and Omogbemile (2013) while in contrast to Srivastava et al (2012). Yadav et al (2012) reported higher diameter values for biscuits having a higher fat content. In the present study, biscuits with higher diameter had higher fat contents significantly (P < 0.05) compared to CB.…”
Section: Physical Properties Of Biscuitssupporting
confidence: 93%
See 1 more Smart Citation
“…This result was in accordance with the results of Nassar et al (2008) and Omoba and Omogbemile (2013) while in contrast to Srivastava et al (2012). Yadav et al (2012) reported higher diameter values for biscuits having a higher fat content. In the present study, biscuits with higher diameter had higher fat contents significantly (P < 0.05) compared to CB.…”
Section: Physical Properties Of Biscuitssupporting
confidence: 93%
“…Yadav et al . () reported higher diameter values for biscuits having a higher fat content. In the present study, biscuits with higher diameter had higher fat contents significantly ( P < 0.05) compared to CB.…”
Section: Resultsmentioning
confidence: 92%
“…Development of nutritious products with oilseeds protein such as defatted soy flour, peanut and cotton seed protein have been extensively studied and reported by various scientists (Khan and Lawhon 1980;Yadav et al 2012). Peanut isolate, concentrates and protein rich flour have received a great attention in recent years to fulfil the increasing demand for high protein food products at affordable price.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some other scientists over the globe who studied the textural features of the cookies prepared with different formulations (Arogba, 2001). In this regard, results of Mamat and Hill (2012) can be correlated who studied the effect of fat types on the structural and textural properties of dough and semi-sweet biscuit (O'Brien et al, 2003;Yadav et al, 2012).…”
Section: Discussionmentioning
confidence: 99%